Here is an example:
log2(83) = 3 ⋅ (log28)
log2(83) = 3 ⋅ 3
log2(83) = 9
Let's check this answer using the definition of logarithms. Since 83 = 512 ,
log2(83) = log2512
And since 29 = 512
log2512 = 9
Thus,
log2(83) = 9
In both cases, the result is 9.
The key to proving this theorem is the following exponentiation property:
xm⋅n = (xm)n
Quiz (1 point)
- x(m ⋅ n) = (xm)n
if logxz = p, then xp = z
if logxz = p, then xp = z
if bn = x, then (bn)p = xp
if the following are true:
- a = x
- b = y
- x = y
then a = b
if bm = bn, then m = n
if n ⋅ p = m, then m = p ⋅ n
if the following are true:
- a = b
- b = c
then a = c
if logbx = n, then p ⋅ (logbx) = p ⋅ n
if the following are true:
- a = c
- b = c
then a = b
Please write your proof in the table below. Each row should contain one claim. The last claim is the statement that you are trying to prove.